That Tumor you're Going to Get Tomorrow … maybe: Making an Informed Decision. Issue 4 (July 2015) - Aitini, Enrico; Adami, Francesca; Barni, Sandro; Zaniboni, Alberto
With the recent progress in predictive medicine several problems have emerged regarding the ethical aspects of genetic testing. The role of the doctor in communicating the consequences of such testing to the patient has become more important than ever in allowing the potential patient to make an informed decision.